Early postnatal maternal trait anxiety is associated with the behavioural outcomes of children born preterm <33 weeks. (December 2020) - Kleine, I.; Falconer, S.; Roth, S.; Counsell, S.J.; Redshaw, M.; Kennea, N.; Edwards, A.D.; Nosarti, C.
Abstract: Maternal ante- and postnatal anxiety have been associated with children's socio-emotional development. Moreover, maternal anxiety has been studied as both a contributing factor and consequence of preterm birth, and children born preterm are more likely to develop behavioural problems compared to term-born controls. This study investigated the association between maternal anxiety measured soon after birth and mental health in 215 ex-preterm children, born at <33 weeks, who participated in the Evaluation of Preterm Imaging Study. Children were followed-up at a median age of 4.6 years (range 4.2–6.6), and received behavioural and cognitive evaluation. Maternal trait anxiety was assessed with the Spielberger State-Trait Anxiety Index at term corrected age. Primary outcome measures were children's Strengths and Difficulties Questionnaire (SDQ) and Social Responsiveness Scale 2 (SRS-2) scores, indicative of generalised psychopathology and autism symptomatology, respectively. IQ was assessed with the Wechsler Preschool and Primary Scales of Intelligence. The final sample, after excluding participants with missing data and multiple pregnancy ( n = 75), consisted of 140 children (51.4% male). Results showed that increased maternal trait anxiety at term corrected age was associated with children's higher SDQ scores (β = 0.25, 95% CI 0.09–0.41, p = 0.003, f 2 = 0.08) and SRS-2 scores (β = 0.15, 95% CI 0.02–0.28, p = 0.03, f 2 = 0.04). Our findings indicate that children born preterm whose mothers are more anxious in the early postnatal period may show poorer mental health outcomes at pre-school age. Further research is needed to investigate preventative measures that can be offered to high-risk premature babies and their families. Highlights: Postnatal maternal anxiety may predict behavioural problems in ex-preterm children. Postnatal maternal anxiety is not associated with IQ in ex-preterm children. Further research needed in the prevention of mental illness in ex-preterm children.